Hot-spots of the genus Aconitum in the Ukrainian Carpathian Region - Novikov, Andriy; Mitka, Józef; Sup-Novikova, Mariia (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2021)
Basing on 2054 georeferenced occurrences of ten Aconitum species, the initial map of the species richness per each of 57 operational geographic units (OGU) of the Ukrainian Carpathian Region (UCR) has been developed. Next, to avoid unequal data distribution, we counted absolute species presence per OGU, based on which we calculated ‘rarity-weighted richness’ (RWR) and performed parsimony analysis. As a result, we found that Chornohora and Svydovets made a strongly supported cluster with the highest Aconitum species diversity and demonstrated the highest RWR values, hence being the main hot-spot of the genus distribution in the UCR. This main hot-spot also spreads to adjacent mountain ranges, including Maramures and Gorgany. Probably, a continuous gradient of Aconitum taxonomic richness from southeast toward northwest of the UCR existed before. The gap in Polonyna Borzhava, located between Polonyna Rivna and Polonyna Rivna, can be secondarily resulted by the high level of anthropogenic transformation of this region. Contrary, the high RWR value and distinct clustering of the Polonyna Rivna supported the presence of a local isolated Aconitum hot-spot related to two prominent mountain peaks located here - Runa-Plai Mt. (in Polonyna Rivna) and Pikui Mt. (in adjacen Waterdivided Mountain Range).